1986
DOI: 10.1007/bf00291884
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of spreading of inactivation in eight X autosome translocations utilizing the high resolution RBG technique

Abstract: Eight X autosome translocations were studied with replication banding to localize spreading of late replication into the autosomal segments. Partial spreading into the autosomal segment was seen in four translocations and no spreading of late replication was seen in four translocations. In those translocations with partial spreading of late replication into the autosomal segment, late replication did not always spread continuously from the X chromosome breakpoint throughout the autosome. Instead, it appeared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 18 publications
4
34
0
Order By: Relevance
“…At least at the cytological level, X inactivation can spread over quite long distances, into autosomal material, in both murine and human X;autosome translocations (e.g., see Disteche et al 1979;Mattei et al 1982;Keitges and Palmer 1986). In addition, ectopic copies of the mouse Xist gene can lead to inactivation of at least some autosomal loci (Lee and Jaenisch 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least at the cytological level, X inactivation can spread over quite long distances, into autosomal material, in both murine and human X;autosome translocations (e.g., see Disteche et al 1979;Mattei et al 1982;Keitges and Palmer 1986). In addition, ectopic copies of the mouse Xist gene can lead to inactivation of at least some autosomal loci (Lee and Jaenisch 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Using this difference in the timing of DNA synthesis, late-replication banding analyses of X;autosome translocations in both mouse and human have revealed that translocated autosomal material becomes later replicating compared with its intact autosomal counterpart and thus appears more like the adjacent inactive X chromosome (Eicher 1970;Disteche et al 1979;Mattei et al 1982;Keitges and Palmer 1986). Additionally, latereplication studies have suggested that the spreading of inactivation into autosomal sequences may be incomplete and discontinuous (Disteche et al 1984;Keitges and Palmer 1986;Schanz and Steinbach 1989). The indirect, subjective nature and low resolution of late-replication banding, however, makes it difficult to draw more than general conclusions about the spreading of X inactivation into autosomal DNA.…”
Section: Introductionmentioning
confidence: 99%
“…As for X-autosome translocation, however, there are many instances that the early replicating regions of translocated autosomal segment replicated in the late S phase due to the "spreading effect" of translocated X chromosome (Camargo and Cervenka, 1984;Keitges and Palmer, 1986). This suggests that each chromosomal region has a feasibility of changing replication timing according to the function of the chromosome in which it is localized.…”
Section: Discussionmentioning
confidence: 99%
“…The X-autosomal translocation is known to change the timing of replication in each chromosomal region accompanied with the change of transcriptional activity (Camargo and Cervenka, 1984;Keitges and Palmer, 1986). Also in plants, changes in transcription have been reported to be caused by chromosome translocation, such as the transcription of nucleolar organizing regions (NOR) in translocation lines of wheat (Rieger et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…(16)(17)(18) A compelling argument has been made for the role of LINE-1 elements, enriched on the mammalian X chromosome, in supporting the spread of silencing. (19,20) The Drosophila X chromosome is enriched in particular satellite sequences and repeats, (21)(22)(23) as is the C. elegans X chromosome.…”
Section: How Important Is Spreading?mentioning
confidence: 99%